Therapeutic Strategies for the Management of Knee Pain – A Review of Current Therapies and Perspectives - Białowąs, Tymoteusz; Karolak, Dominika; Kuśmierowska, Natalia Sara; Kuś, Monika; Słomkowski, Grzegorz; Cholewiński, Kacper; Valipur Kolti, Daria; Polak, Milena; Nowak, Magdalena Natalia; Wiśniewski, Konrad (Quality in Sport, 2026)
Background. Knee pain can significantly impact patients’ quality of life. Pain emerging with age is most commonly associated with osteoarthritis of the knee. Aim. Current clinical management comprises three lines of treatment. Results. The first and second lines focus on conservative and pharmacological management, while the third involves surgical intervention. Conclusions. This paper discusses both current therapeutic standards and innovative treatment methods.